The influence of endocrine disruptors on the gut microbiota - Ugur, Kader (Tubitak Scientific & Technological Research Council Turkey, 2025)
Endocrine disruptors (EDs) are closely associated with the second brain, the microbiota-derived enteric nervous system, commonly referred to as the gut microbiota. The microbiota plays a crucial role in human health and the development of diseases. In today's industrialized world, the presence of EDs in air, water, and soil leads to primary human exposure through dermal contact and ingestion. The impact of these EDs on the microbiota remains unclear. EDs that disrupt the balance of the gut microbiota may contribute to a range of disorders, including metabolic (obesity, diabetes mellitus), cardiovascular (vascular stenosis, cerebrovascular disease), reproductive (infertility, ovarian and testicular tumors), neurological (dysfunction of the amygdala, cortex, and cerebellum), and behavioral disorders (dementia, depression, anxiety, and schizophrenia). This review examines the effects of commonly encountered environmental EDs on the gut microbiota and summarizes the most recent findings on this topic. The concept of the microbiota-derived enteric nervous system and the modulation of the hormonal system through interactions between microorganisms and environmental chemicals have prompted specialists in endocrinology and metabolism to reconsider patient management and treatment strategies. This necessitates a comprehensive evaluation of treatment options that incorporate microbiome data. The information presented in this review will help illuminate future research directions and serve as a valuable resource for subsequent studies.
Keywords: Endocrine disruptors; gut; microbiota; human health